Expediting Discharge in Hospitalized, Adult Patients with Skin and Soft Tissue Infections Who Received Empiric Vancomycin Therapy with Oritavancin: Description of Findings from an Institutional Pathway - Cristen Whittaker; Thomas P. Lodise; Ethan Nhan; Joseph Reilly (Adis, Springer Healthcare, 2020)
Abstract Background An internal quality assurance review at AtlantiCare Regional Medical Center (ARMC) revealed that patients admitted with skin and soft tissue infections (SSTIs) remained in hospital post-resolution of acute symptoms and demonstrated a delayed transition to step-down oral antibiotic therapy. A non-mandatory institutional pathway was developed and implemented in 2016 to expedite hospital discharge in hemodynamically stable SSTI patients by utilizing oritavancin. Objective To describe the outcomes associated with use of single-dose oritavancin therapy to expedite hospital discharge in hemodynamically stable inpatients with SSTIs. Methods A retrospective, descriptive cohort was evaluated for outcomes of patients with SSTIs who received either oritavancin to expedite discharge or were discharged on oral step-down antibiotics. Patients were included in this analysis if they were: ≥ 18 years old; hospitalized; received empiric vancomycin; not pregnant or nursing; hemodynamically stable at the time of assessment; and received either oritavancin or oral step-down antibiotics to facilitate discharge. The primary outcomes were index hospital length of stay (LOS), 30-day SSTI-related readmissions, and 30-day SSTI progression. Results Overall, 199 patients met the study criteria (oritavancin = 99 and oral step-down antibiotics = 100). Groups were well matched at baseline. Patients who received oritavancin had a shorter mean index hospital LOS than those in the oral step-down antibiotic group (3.5 days vs. 5.6 days). Patients receiving oritavancin also had lower SSTI 30-day readmission and SSTI-progression rates. Conclusions An institutional pathway that used oritavancin to expedite hospital discharge of hemodynamically stable SSTI patients resulted in shorter hospital LOS, less 30-day SSTI-related hospital readmissions, and decreased SSTI progression relative to those discharged on conventional oral step-down therapy.